Multicenter experience with the Evolution RL mechanical sheath for lead extraction using a stepwise approach: Safety, effectiveness, and outcome. Issue 7 (2nd May 2019) - Migliore, Federico; Testolina, Martina; Sagone, Antonio; Carretta, Domenico; Agricola, Tullio; Rovaris, Giovanni; Piazzi, Elena; Facchin, Domenico; De Lazzari, Manuel; Zorzi, Alessandro; Melillo, Francesco; Cataldi, Claudia; et al.
Abstract: Background: In addition to the Evolution RL sheath, tools by Cook Medical (Bloomington, IN, USA), supporting lead extraction (LE), are available. Data on their use are not reported in detail in previous studies. Moreover, data regarding outcome are lacking. The aim was to evaluate the safety and effectiveness of the Evolution sheath (Evolution RL and Evolution Shortie, Cook Medical) by using a stepwise approach with the available extraction tools and the outcome. Methods: A total of 393 leads in 198 consecutive patients were removed with the Evolution RL sheath and ancillary tools using a stepwise approach. Results: The main indication for LE was infection in 125 (63.1%) cases. The mean implant duration was 95.4 ± 59.7 months. According to our stepwise approach, the Evolution Shortie RL sheath was used in all cases and complete LE was achieved in 24 (12.2%) cases. The Evolution RL was used in 174 (87.8%) cases and the SteadySheath Evolution tissue stabilization sheath (Cook Medical) in 87 (44%) because of tenacious fibrosis anchored targeted leads. Compression coil (OneTie, Cook Medical) was used in 141 (71%) cases. Complete procedural success rate, clinical success rate, and lead removal with clinical success rate were 97%, 99%, and 99.5%, respectively. One major complication (0.5%) and 10 (5%) minor complications were encountered. During a mean time follow‐up of 12 ± 9 months, 14 (7%) patients died. Predictors of mortality included impaired renal function (HR 5.7; 95% CI 1.9–17.6; P = 0.002), extraction because of infection (hazard ratio [HR] 4.0; 95% confidence interval [CI] 1–18.1; P = 0.045), and diabetes (HR 3.2; 95% CI 1.1–9.8; P = 0.036). Conclusions: Lead extraction using the Evolution RL bidirectional rotational mechanical sheath and ancillary tools in a systematic stepwise approach was effective and safe.